Competence and Performance of Clinical Instructors during the Implementation of Group E-Mentoring for the Optimization of Student Guidance - Yusnaini Yusnaini; Dina Andriani Br. Karo; Muasir Pagan; Nandara Priyanti Elna; Tri Ratnaningsih (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Competency-based nursing education requires students to master clinical skills critical to workforce readiness; however, challenges persist in the field practicum due to limited structured guidance. This study addresses the lack of research on the effectiveness of structured digital e-mentoring programs in Indonesian clinical settings. The purpose was to evaluate the impact of group e-mentoring on the competence and performance of clinical instructors in supporting nursing student guidance at Nurul Hasanah Hospital, Kutacane. A quantitative quasi-experimental design with a pre- and post-test (without control group) was used. Total sampling based on inclusion criteria resulted in 60 respondents, including clinical instructors and nursing students. Competence was measured using the Mentor Competencies Instrument (MCI), and performance was assessed with the Nurse Mentor Performance Assessment tool. Data analysis employed the Wilcoxon signed-rank test to compare pre- and post-intervention scores. Results demonstrated statistically significant improvements in competence (mean increased from 115.2 to 148.3) and performance (mean increased from 55.8 to 66.2), with p-values of 0.000 and 0.001 respectively, indicating a positive effect of preceptorship and mentorship training integrated within the group e-mentoring program. These findings suggest that structured digital e-mentoring enhances clinical instructors' ability to provide effective student guidance, optimizing clinical education in resource-limited settings.